Jacob Böhme and his world - Andersson, Bo 1955-; Martin, Lucinda 1965-; Penman, Leigh T. I. 1979-; Weeks, Andrew 1947- (Brill, 2019)
Jacob Boehme (1575-1624) is famous as a shoemaker and spiritual author. His works and thought are frequently studied as a product of his mystical illumination. Jacob Boehme and His World adopts a different perspective. It seeks to demystify Boehme by focusing on aspects of his immediate cultural and social context and the intellectual currents of his time, including Boehme's writing as literature, the social conditions in Goerlitz, Boehme's correspondence networks, a contemporary "crisis of Piety", Paracelsian and Kabbalistic currents, astrology, astronomy and alchemy, and his relationship to other dissenting authors. Relevant facets of reception include Boehme's philosophical standing, his contributions to pre-Pietism, and early English translations of his works
Keywords: Böhme, Jakob -- 1575-1624; Böhme, Jakob; Böhme, Jakob / 1575-1624; Konferenzschrift -- 2014 -- Görlitz